A presença como artefato do discurso: a relação entre participação e representação nos Conselhos Gestores. - Alexander Cambraia Nascimento Vaz (2008)
This dissertation has been elaborated with the objective of discussing the representative acting of individuals in the so called Policy Councils. These institutions are spaces created through the 1988 Constitution that facilitates the direct negotiation between state and civil society in matters of specific public policies. In this sense, its actors are given the power to influence or even make decisions that may affect others individuals lives. The literature that deals with this thematic has been focusing on both the increase of participation itself and its possible impacts on the politicaldynamics of society, as well as on the functioning of the participatory institutions and factors that may affect it. Little attention has been given to the fact that, actually, participation is only possible in through the adoption of representative mechanisms. Then, it´s been researched here the basis of legitimacy of those individuals that play the role of civil society counselors. Preliminary results have pointed that, much more than being restricted to an authorizative moment, this legitimacy seems to be linked to the capacity of counselors to be in contact with the basis, the represented, although this contact should be understood as a moment for general orientation for his/her acts, and not for specific determinations of his/her actions.